Factors Responsible for Students' Lateness to School as Expressed by Nigerian Teachers in Elementary Schools - Adegunju, Kabir Adewale; Ola-Alani, Eniola Keji; Agubosi, Lydia Akunna (Mimbar Sekolah Dasar, 2019)
Students lateness to school is one of the challenges faced by school administrators. This research therefore investigated the factors responsible for students lateness to school as expressed by Nigerian teachers in elementary schools. The influence of moderating variables of sex, years of teaching experience and educational qualification on the respondents expressions was also considered. The study is descriptive in nature and sampled 200 Nigerian teachers in elementary schools. An instrument titled Factors Responsible for Lateness to School Questionnaire (FRLSQ was adopted to gather data. The descriptive and inferential statistics were used as methods of data analysis. It was revealed that the factors responsible for students lateness to school as expressed by Nigerian teachers in elementary schools are poor preparation for school, going late to bed, distance of school from home, high level of poverty, peer pressure, single parenting among others. It is concluded that the factors responsible for lateness to school are enormous. Practical solutions were therefore recommended.